Perceived utility of experiential learning programme of Indian Council of Agricultural Research - LEKANG, BUSHE; NAIN, M S; SINGH, RASHMI; SHARMA, J P (The Indian Journal of Agricultural Sciences, 2016)
Youth unemployment is a global concern, attributed among others to lack of appropriate skills. Skills-focused education has been found to be an appropriate tool to fill the void. Indian Council of Agricultural Research heeded to this by introducing a programme in 2006 named Experiential Learning Programme the aim which was to equip undergraduates with entrepreneurial skills. The programme has been running for a decade since its inception, hence its evaluation comes at a rightful time. An ex-post facto study aimed at finding out among students and teachers how useful the programme had been in imparting entrepreneurial skills and competencies as well as to enable students to go through all entrepreneurial education stages was conducted in six agricultural universities in North India. The findings revealed that the programme was perceived useful by both students and teachers in imparting entrepreneurial skills, entrepreneurial competencies and allowed students to go through all stages of entrepreneurial education. Significant differences of usefulness of the programme as perceived by students from different disciplines were noted. Generally there were significant differences on perceived utility on the basis of personal characteristics of respondents, except for students’ sex and age. Students had little intention of venturing into self-employment, whereas teachers indicated that none of their graduates had established an enterprise. Even though the programme had been perceived useful in equipping graduates with the necessary entrepreneurial skills and competencies, graduates were not yet motivated to venture into self-employment. Therefore, there is need to review the programme and provide start-up fund at institutions which can assist students to go through all stages of entrepreneurship education as well as lure graduates into self-employment.